Episodic Ataxia Type 1 (K‐channelopathy) Manifesting as Paroxysmal Nonkinesogenic Dyskinesia: Expanding the Phenotype. Issue 5 (31st July 2017) - Set, Kallol K.; Ghosh, Debabrata; Huq, A.H.M.; Luat, Aimee F.
Abstract : View Supplementary Video 1